The response of plant functional traits to aridity in a tropical dry forest - de Oliveira, Ana Cláudia Pereira (2020)
Drylands are experiencing an overall increase in aridity that is predicted to intensify in the future due to climate change. This may cause changes in the structure and functioning of dryland ecosystems, affecting ecosystem services and human well-being. Therefore, detecting early signs of ecosystem change before irreversible damage takes place is important. Thus, here we used a space-for-time substitution approach to study the response of the plant community to aridity in a Tropical dry forest (Caatinga, Brazil), and infer potential consequences of climate change. We assessed plant functional structure using the community weighted mean (CWM) and functional diversity, measured through functional dispersion (FDis), along a 700 km climatic gradient. We studied 13 functional traits, reflecting strategies associated with establishment, defense, regeneration, and dispersal of the most abundant 48 plant species in 113 sampling sites. Spearman correlations were used to test the relation between aridity and single-trait functional metrics. Aridity was a major environmental filter of the plant community functional structure. We found a higher abundance of species with deciduous leaves, zoochorous dispersal, fleshy fruits, chemical defense exudation and spinescence, and crassulacean acid metabolism towards more arid sites, at the expense of species with evergreen and thicker leaves, autochory dispersal, and shrub growth-form. The FDis of leaf type and thickness decreased with aridity, whereas FDis of fruit type, photosynthetic pathway, and defense strategies increased. Our findings provide functional indicators to early detect climate change impacts on Caatinga structure and functioning, to timely adopt preventive measures (e.g. conservation of forest remnants) and restoration actions (e.g. introduction of species with specific functional traits) in this threatened and unique ecosystem.